Cleft lip and palate genetics and application in early embryological development - Wenli Yu; Maria Serrano; Symone San Miguel; L. Bruno Ruest; Kathy K. H. Svoboda (Indian Journal of Plastic Surgery)
The development of the head involves the interaction of several cell populations and coordination of cell signalling pathways, which when disrupted can cause defects such as facial clefts. This review concentrates on genetic contributions to facial clefts with and without cleft palate (CP). An overview of early palatal development with emphasis on muscle and bone development is blended with the effects of environmental insults and known genetic mutations that impact human palatal development. An extensive table of known genes in syndromic and non-syndromic CP, with or without cleft lip (CL), is provided. We have also included some genes that have been identified in environmental risk factors for CP/L. We include primary and review references on this topic.